CRITICAL THEORY AND SOCIAL SCIENCE: A PHILOSOPHICAL COMPARISON OF HERBERT MARCUSE AND JÜRGEN HABERMAS - Nidzom, Muhammad Faqih; Muslih, Mohammad; Falah, Muhammad Zulfikar Nur (Sekolah Tinggi Agama Islam Sadra, 2025)
This research addresses the contemporary global conflict surrounding transformations in social life through the lens of Critical Theory. The urgency of analyzing the thoughts of Herbert Marcuse and Jürgen Habermas lies in their critical engagement with the rational foundations of the modern social system. This study aims to conduct a comparative analysis of Marcuse’s and Habermas’s contributions to Critical Theory. The material object of this study is Critical Theory in social science, while the formal object focuses on the specific theories developed by Marcuse and Habermas. Employing a library research method and a comparative approach. Data processing in this study uses descriptive analysis, which means describing the data sources of Marcuse and Habermas’ Critical Theory, then analyzing the descriptive data sources from both Critical Theory thinkers. Marcuse’s key concept is the “one-dimensional man,” reflecting a critique of advanced industrial society, whereas Habermas introduces “communicative action” as a foundation for rational discourse in democratic societies. The differences in these concepts are shaped by their distinct philosophical and socio-historical contexts. The study concludes that Marcuse’s and Habermas’s theories represent a dialectical tension: Marcuse as a thesis with a monolithic representation of modern rationality (instrumental rationality that is adaptive with control, efficiency, and domination), Habermas as an antithesis with a typological representation of instrumental rationality and communicative rationality. Habermas does not reject instrumental rationality, but limits it only to non-human objects. When applied to humans, instrumental rationality causes social pathology. Their synthesis lies in recognizing the role of identity and intersubjective recognition in fostering communicative action. This study implies that the Islamic context in Marcuse and Habermas’ discourse leads to conceptual prospects for social cohesion and justice.